Hand Osteoarthritis: investigating Pain Effects of estrogen-containing therapy (HOPE-e): a protocol for a feasibility randomised placebo-controlled trial - Marian, IR; Goff, M; Williams, J; Gulati, M; Chester-Jones, M; Francis, A; Watson, M; Vincent, T; Woollacott, S; Mackworth-Young, C; Glover, V; Furniss, D; et al. (BioMed Central, 2021)
Background: Hand osteoarthritis (OA) is a common condition, causing pain, stiffness and reduced quality of life. Incidence is higher amongst women, particularly around the age of the menopause. Whilst the relationship between sex hormones and OA has been studied in vitro, in epidemiological studies and in clinical trials of hormone replacement therapy (HRT), this study is the first to investigate the effect of estrogen-containing therapy on hand pain in post-menopausal women with symptomatic hand OA in a randomised study design. Methods: This is a feasibility study of a double-blinded placebo-controlled intervention with 1:1 randomisation to either a combination of conjugated estrogens 0.45 mg and bazedoxifene acetate 20 mg (Duavive) or placebo. The target population is post-menopausal women with symptomatic hand OA, aiming to recruit 60–90 study participants. The primary objective is to assess the feasibility of a future fully powered randomised controlled trial (RCT). Participants will take the study medication for 24 weeks and be followed up for 28 weeks after randomisation. The primary outcomes used to determine feasibility are eligible participant identification rates and routes; recruitment, randomisation and retention rates of eligible participants; study medication compliance; and the likelihood of unintentional unblinding. Secondary outcomes include measures of hand pain, function, appearance and menopausal symptoms. An end of study questionnaire and focus groups will help to refine the final protocol for a full study. Discussion: Identifying new treatments for symptomatic hand OA is a recognised research priority. The study will help us to understand whether there are sufficient interested and eligible individuals in this target population who would consider HRT for their hand symptoms. It will provide proof-of-concept RCT data on the effects of HRT on hand pain and other clinically relevant outcomes in this population. The study will gain valuable information on the feasibility of a full RCT and how best to run this. The findings will be published in a peer-reviewed journal and presented at a relevant conference. Trial registration: ISRCTN12196200 registered on 15 January 2019